ICT Adoption in Moroccan Higher Education: Key Predictors of Students’ Technology Acceptance and Usage - Soumia El Hazzat; Yamina EL KIRAT EL ALLAME; Rdouan FAIZI (Moroccan Journal of Quantitative and Qualitative Research)
Despite the recent widespread integration of digital technologies in higher education, there’s still a noticeable gap in research pertaining to this phenomenon within the context of developing nations, such as Morocco. This study investigates the key factors influencing students' usage of Information and Communication Technologies (ICT) within the context of Moroccan higher education, using an extended version of the Unified Theory of Acceptance and Use of Technology (UTAUT) as a theoretical framework. The UTAUT is extended to adapt to the Moroccan context by incorporating self-efficacy into the model’s constructs. The study addresses three main research questions (i) How do performance expectancy and effort expectancy influence Moroccan university students' intentions toward ICT adoption? (ii) to what extent do the constructs of social influence and facilitating conditions shape students' intention to engage with ICT? (iii) How does self-efficacy impact students' acceptance and usage of ICT in higher education? The study adopted a quantitative approach. A questionnaire was administered to 354 students and analyzed using multivariate statistical methods. The findings revealed that performance expectancy, effort expectancy, and self-efficacy are the most significant predictors of students’ ICT adoption, while social influence and facilitating conditions have minimal impact. This suggests that students are more likely to adopt ICT tools if they find them easy to use, beneficial for their learning, and feel confident in their ability to utilize them.